NIGHTSONG: POWER AND PRACTICE IN SOUTH AFRICA, by Veit Erlmann, Chicago, London: University of Chicago Press 1996 - Impey, Angela (International Library of African Music, 1999)
pages: 193-195
Keywords: South Africa; African Music